Electrospun Ultrafine Cationic Cellulose Fibers Produced from Sugarcane Bagasse for Potential Textile Applications - Andrés Felipe Ochica Larrota (MDPI AG, 2021)
Sugarcane bagasse (SCB) is an abundant by-product of sugar refining that can be utilized as a raw material for cellulose isolation for several industrial applications. Electrospinning has garnered attention in recent years because it allows the preparation of cellulosic materials with unique properties. In this study, cellulose was isolated from sugarcane bagasse and acetylated to fabricate fine acetate cellulose fibers through electrospinning. Subsequently, the electrospun fibers were deacetylated and cationized in order to produce functionalized materials with potential textile applications. The functional fibers were colored with an anionic dye (vinyl sulfone) with and without the presence of salt and were evaluated according to dye fixation, color attributes, morphological characteristics, and thermal stability. Cationic cellulose fibers that were dyed without added salt were found to be brighter and demonstrated better color fixation than those with added salt. In addition, morphological analysis performed using scanning electron microscopy demonstrated that cationized fibers dyed without added salt were better preserved at this stage. The cationic fiber also evidenced a high-temperature resistance, exhibiting a degradation temperature above 236 °C. The results suggest that cellulose fibers dyed in this manner can potentially be considered for use in textile applications due to their suitable dye fixation and tunable porosity (i.e., breathability).